A profile study of 1016 drug addicts in Malaysia - Gyanchand Rampal, Lekhraj Rampal; Md. Zain, Azhar; Lekhraj Rampal, Sanjay Rampal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
Introduction: A cross-sectioned study was carried out on 1016 drug addicts from Johor state to better understand their profile. Methods: A structured questionnaire prepared in three languages was used to collect the data which was analysed using the Statistical Package for Social Sciences. Result& Discussion: The overall mean age of the respondents was 33.8 (95% CI=33.3-34.4) years and ranged from 16 to 61 years. ANOVA post hoc multiple comparison tests showed that was a significant different in the mean age between Malays and Chinese (p<0.0001) and Malays and Indians (p<0.0001). However, there was no significant different in the mean ages between Chinese and Indians (p<0.05). The majority of the respondents were Malay (79.6%) and had secondary education (72.1%) or primary education (21.7%). The majority (79%) was either semi-skilled or unskilled. More than 70% had more than five siblings. About 36% of the respondents had past a history of discipline problem at school. The majority (99.6%) of the drug addicts had smoke before and more than 90% were currently smoking. More than 80% had consumed alcoholic beverages. The majority did not used condom when they had sex. Only 24% stated that they did use a needle or syringe that had previously been used by someone else. Less than 4% had either bleached or boiled the needle or syringe that had previously been used someone else. About 17% were tested positive for HIV. The mean age at which the respondents first started injecting drugs was 21.5 (95% CI=20.7-22.2) years. ANOVA post hoc multiple comparison tests showed that there was no significant different in the mean age of the different ethnic groups at which the respondents first started injecting drugs. The majority (84.2%) of the drug addicts started injecting drugs between 10 and 20 years of age. Friends introduced 80% of drug addicts to drug. The common reasons given for first taking drugs was “I was curious about the feeling of taking drugs(43.6%)”, “ My friends asked me to try” (23.4%), “to release tension” (15.6%) and 5% stated “ to try for fun”, and 3% that they were “depressed”. The majority (64.2%) of drug addicts spend RM500 or more on drug and, more than 10% of them spend as much as RM1000 or more per month. Conclusion: These results indicate an urgent need for a more comprehensive program involving family, schools, communities and the media and aimed at reducing drug abuse.